Emotional Well-Being: What It Is and Why It Matters - Park, Crystal L.; Kubzansky, Laura D.; Chafouleas, Sandra M.; Davidson, Richard J.; Keltner, Dacher; Parsafar, Parisa; Conwell, Yeates; Martin, Michelle Y.; Hanmer, Janel; Wang, Kuan Hong (Affective science, 2023)
Psychological aspects of well-being are increasingly recognized and studied as fundamental components of healthy human functioning. However, this body of work is fragmented, with many different conceptualizations and terms being used (e.g., subjective well-being, psychological well-being). We describe the development of a provisional conceptualization of this form of well-being, here termed emotional well-being (EWB), leveraging prior conceptual and theoretical approaches. Our developmental process included review of related concepts and definitions from multiple disciplines, engagement with subject matter experts, consideration of essential properties across definitions, and concept mapping. Our conceptualization provides insight into key strengths and gaps in existing perspectives on this form of well-being, setting a foundation for evaluating assessment approaches, enhancing our understanding of the causes and consequences of EWB, and, ultimately, developing effective intervention strategies that promote EWB. We argue that this foundation is essential for developing a more cohesive and informative body of work on EWB.